(untitled) (Materiali di Estetica. Terza serie, 2019)
This paper examines some of the Anti-Trinitarian interpretations on God’s words.It starts from the expulsion from the Garden of Eden, seen according to a Hebrew commentary, the one of Erich From,up to some heretics of 1500 who challenged the Trinity, according to a philological reading of the Scriptures, cleared of some of the encrustations due to the tradition. The paper deals with Serveto, Biandrata, and Ferenc David, but mentions also the survival of some of the Anti-Trinitarian theses in the philosophy of Ralph W. Emerson, a philosopher who had a not negligible weight in the development of the American culture of the nineteenth century. One of the last heirs of this tradition is the Jesuit Roger Lenaers, who considers it appropriate to refer to the Anti- trinitarian ideas, to give new life to the living word of God, in a world that he considers desecrated. Beyond the utopias, however, we should not forget the violent aspects that have always been linked to the word of God, of which we have seen some examples here.